1956
DOI: 10.1063/1.1743165
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen as a Donor in Zinc Oxide

Abstract: Hydrogen is found to diffuse into and increase the conductivity of single ZnO crystals. The diffusion rates have been obtained, as well as the temperature and pressure dependencies of the quantity of hydrogen in the crystal. This quantity is found to be influenced by the electrons already in the crystal. It is thought likely that hydroxyl groups are formed from the hydrogen and oxide ions. The donor center has an ionization energy of 0.04 ev.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
157
1
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 308 publications
(176 citation statements)
references
References 5 publications
16
157
1
2
Order By: Relevance
“…Those results, however, went largely unnoticed during the upsurge in research activity on hydrogen in semiconductors that started about 30 years later. Mollwo [11] observed an increase in the conductivity of ZnO crystals exposed to hydrogen at temperatures above 200 ± C. The increase in the conductivity was demonstrated to be due to indiffusion of hydrogen, for which an activation energy of 0.91 eV was measured [11,12]. An increase in conductivity upon exposure to H 2 was also observed by Baik et al [14], and by Kohiki et al [15] who introduced hydrogen by proton implantation followed by annealing at 200 ± C. All of these experimental results indicate that introducing hydrogen into ZnO does not result in a reduction of the conductivity, which is the expected behavior for hydrogen in other semiconductors.…”
Section: (Received 3 February 2000)mentioning
confidence: 99%
See 1 more Smart Citation
“…Those results, however, went largely unnoticed during the upsurge in research activity on hydrogen in semiconductors that started about 30 years later. Mollwo [11] observed an increase in the conductivity of ZnO crystals exposed to hydrogen at temperatures above 200 ± C. The increase in the conductivity was demonstrated to be due to indiffusion of hydrogen, for which an activation energy of 0.91 eV was measured [11,12]. An increase in conductivity upon exposure to H 2 was also observed by Baik et al [14], and by Kohiki et al [15] who introduced hydrogen by proton implantation followed by annealing at 200 ± C. All of these experimental results indicate that introducing hydrogen into ZnO does not result in a reduction of the conductivity, which is the expected behavior for hydrogen in other semiconductors.…”
Section: (Received 3 February 2000)mentioning
confidence: 99%
“…Experimental indications for hydrogen's behavior as a donor in ZnO were reported in the 1950s [11][12][13], ZnO being the first semiconductor in which the properties of hydrogen were systematically studied. Those results, however, went largely unnoticed during the upsurge in research activity on hydrogen in semiconductors that started about 30 years later.…”
Section: (Received 3 February 2000)mentioning
confidence: 99%
“…This reaction was reported for ZnO already in the 1950s [7], and it was found that protons and electrons were the dominating defects in hydrogen atmospheres, so that the electroneutrality condition and concentrations are expressed as:…”
Section: Defect Structures Of Proton-conducting Oxidesmentioning
confidence: 99%
“…For example, in the 1950's hydrogen was known to give rise to shallow donors in ZnO. [7][8][9] Transparent conducting oxides have unusual but highly useful properties, combining transparency in the visible region of the spectrum with high electrical conductivity. [10][11][12] Native defects such as O vacancies and cation interstitials have been frequently invoked as possible sources of n-type conductivity.…”
Section: Introductionmentioning
confidence: 99%